The meaning of being a pharmacist: Considering the professional identity development of firstyear pharmacy students - M van Huyssteen; A Bheekie (South African Medical Association, 2015)
Background. Professional identity underpins an individual’s perspective in the way they evaluate, learn and make sense of their professional practice. In pharmacy education, the development of a professional identity has remained problematic, which may largely be attributed to the dearth of literature that properly defines, teaches and assesses professionalism. Objectives. To identify and describe first-year pharmacy students’ professional identity and determine whether it changed during the first semester of the ‘Introduction to pharmacy’ course. Methods. Students had to write three sequential reflective reports in which they were expected to identify critical experiences since their enrolment. These served as reference points from which they could frame their sense of professional identity. After grading, each set of reports was ordered according to total marks allocated, of which every tenth report was selected for thematic analysis. Results. Baseline reports indicated that students had a largely stereotypical view of the pharmacist as medicine supplier. Subsequent reports showed a shift in perspective, as students articulated a more complex role for the pharmacist, distinguished between the pharmacist’s role and that of other health professionals, and formulated the pharmacist’s positive value for society. Conclusion. Our findings describe the attempts of first-year pharmacy students to internalise a professional identity during a first-semester module. By applying concepts of social identity theory to sequential reflective assignments, an emerging professional identity could be interpreted, which was denoted by an increasing sense of belonging to the pharmacy profession.